2022
DOI: 10.3390/bs12060195
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation for the Treatment of Resistant Depression: A Scoping Review

Abstract: Treatment-resistant depression (TRD) is associated with significant disability, and due to its high prevalence, it results in a substantive socio-economic burden at a global level. TRD is the inability to accomplish and/or achieve remission after an adequate trial of antidepressant treatments. Studies comparing repetitive transcranial magnetic stimulation (rTMS) with electroconvulsive therapy (ECT) and pharmacotherapy have revealed evidence of the therapeutic efficacy of rTMS in TRD. These findings suggest a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Results from systematic reviews and meta‐analyses consistently support the efficacy of rTMS in TRD 233 . Results also indicate that greater severity at baseline and higher number of prior antidepressant failures are associated with attenuated rTMS efficacy 239‐243 .…”
Section: Management Of Treatment‐resistant Depressionmentioning
confidence: 75%
See 1 more Smart Citation
“…Results from systematic reviews and meta‐analyses consistently support the efficacy of rTMS in TRD 233 . Results also indicate that greater severity at baseline and higher number of prior antidepressant failures are associated with attenuated rTMS efficacy 239‐243 .…”
Section: Management Of Treatment‐resistant Depressionmentioning
confidence: 75%
“…Neurostimulatory treatments evaluated in TRD include vagus nerve stimulation (VNS), ECT, rTMS, magnetic seizure therapy, deep brain stimulation, and transcranial direct current stimulation [227][228][229][230][231][232][233] .…”
Section: Neurostimulationmentioning
confidence: 99%
“…2 b the percent not showing improvement after four weeks is about 17% which corresponds almost exactly to the percentage of patients with less than 5% PCL-5 improvement, i.e., no treatment response, with PrTMS. Interestingly, a recent (2022) retrospective literature meta-analysis of rTMS in depression indicated that a 4–6 week treatment duration yields tangible results, and Carpenter and co-workers (2017) reported that significant antidepressant effects were obtained after 4 weeks of rTMS [ 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other researchers modified the treatment technology based on problems encountered during the development process. They elaborated a treatment method called repetitive TMS (rTMS) that transmits TMS with repetitive pulses at short intervals[ 18 ]. In the past five years, researchers have used rTMS to treat many neurological and mental health conditions to study and evaluate its therapeutic effect[ 19 - 21 ].…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%